IgM-enriched human intravenous immunoglobulin suppresses T lymphocyte functions in vitro and delays the activation of T lymphocytes in hu-SCID mice - Vassilev, T (Blackwell Science Inc, 2006)
Previous studies of an experimental human immunoglobulin preparation for intravenous use, containing normal pooled IgM (IVIgM), have shown its beneficial therapeutic effect in experimental autoimmune diseases. The mechanisms of its immunomodulatory activity remain however, poorly understood. In the experiments reported here, IVIgM inhibited the proliferation of various autonomously growing human lymphoid cell lines in vitro, as well as of MLR- and of PHA-stimulated human T-lymphocytes. These effects of IVIgM were observed at non-apoptotic concentrations and were stronger on a molar basis than those of normal pooled IgG for intravenous use (IVIg). Both preparations, when administered to SCID mice, repopulated with human peripheral blood mononuclear cells, delayed the expression of the early activation marker CD69 on both human CD4+ and CD8+ T-lymphocytes, activated by the mouse antigenic environment. The data obtained show that normal pooled human IgM exerts a powerful antiproliferative effect on T-cells that is qualitatively similar but quantitatively superior to that of therapeutic IVIg. Our results suggest that infusions with IVIgM might have a significant beneficial immunomodulating activity in patients with selected autoimmune diseases.